The effects of benzo(a)pyrene, nicotine, and tobacco-specific N-nitrosamines on the generation of human lymphokine-activated killer cells - Lindemann, R A; Park, N H (Archives of oral biology, 1989)
The effects of four major components of snuff (fine-cut smokeless tobacco) on the development of lymphokine-activated killer cells (LAK) were measured in vitro. Of the components tested: nicotine, N'-nitrosonornicotine, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone and benzo(a)pyrene (BaP), only BaP suppressed LAK cytotoxicity against tumour targets and LAK DNA synthesis during 3- and 7-day incubations. BaP concentrations of 0.1-1.0 micrograms/ml suppressed lymphocyte proliferation only; there was no effect on tumour cell proliferation at these concentrations. BaP had no effect on tumour target killing when incubated during 4 h natural killer (NK) or LAK cytotoxicity assays. There was no effect on LAK binding of tumour targets after 3 days culture with BaP concentration of 0.1-1.0 micrograms/ml. These data confirm that a water-soluble extract of snuff has anti-cytolytic and anti-proliferative effects on peripheral blood lymphocytes. As NK and LAK cells are important in preventing tumourigenesis and metastasis, suppression of these cells may favour neoplastic growth associated with snuff-dipping.